Development of a tesfilit model in the Student Physical Fitness course - Saisada, Siska; iyakrus, Iyakrus; Usra, Meirizal (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research aims to produce a web-based application model as an application that can be used in student physical fitness courses. The method used in this study is the R & D (Research and Depelopment) method which is research that produces products and perfects existing products in the form of test model applications. The research used was a development of Borg & Gall. From the results of the trial, the results of the evaluation of material experts were obtained which were 3.7 which were included in the very valid category and media experts received a score of 3.7 which was included in the very valid category. The results of small-scale trials get a score of 4.57 which is included in the very practical category. The results of large-scale trials get a score of 4.60 which is included in the very practical category. The results of product effectiveness get a value of 4.9 which is included in the category of very effective